Positive Solutions for Elliptic Boundary Value Problems with a Harnack-Like Property - Moussaoui, Toufik; Precup, Radu (CUBO, A Mathematical Journal, 2008)
The aim of this paper is to present some existence results of positive solutions for elliptic equations and systems on bounded domains of â„N (N â‰¥ 1). The main tool is Krasnosel‘skii‘s compression-expansion fixed point theorem.